COGNITIVE DEVELOPMENT BASED ON THE VOLLEYBALL GAME PLAY IN PHYSICAL EDUCATION (International Journal of Physiotherapy, 2020)
Background: The purpose of this study is to determine the effects of the Teaching Games for Understanding (TGfU), Sport Education Model (SEM), and Hybrid Teaching Games for Understanding Sport Education Model (HTGfU–SEM) on the cognitive performance among Form 1 students on volleyball gameplay. Student’s cognitive focusing on the tactical decision-making aspect of opening and closing space and selection of skills used in the game.Methodology: The study is using the quasi-experimental method involving a sample of 96 Form 1 students. The control group is TGfU while the treatment groups are SEM and HTGfU-SEM. The research instrument was adapted from the Game Performance Assessment Instrument (GPAI) with the validity value (r =.81). These modified instruments were used to assess the cognitive aspects of badminton gameplay. The Mean, SD, ANOVA, ANCOVA, MANOVA and posthoc test were used to analyze the cognitive data.Results: As for the overall tactical decision making via a multivariate test in volleyball gameplay indicated significant effect through SEM. Especially for closing space in volleyball 3 vs. 3 gameplay through SEM, F (2, 93) = 10.054, p